Edward Burr papers - Burr, Edward, 1859-1952.
Correspondence, military papers, scholastic records, printed materials, memorabilia, and photographs, relating chiefly to Burr's career in the U.S. Army Engineer Corps (1882-1898). Documents his service as assistant engineer of canal construction on the Columbia River (Portland and Cascade Locks, Or.), as inspector of the construction of lock gates (Cascade Locks, Or.), as supervisor of river and harbor improvements (Norfolk, Va.), and as assistant to the Engineer Commissioner of the District of Columbia. Also includes Burr's records while a student at Washington University, Saint Louis, Mo., and West Point Military Academy. Correspondents include Francis Collingwood, Wm. P. Craighill, William B. Dennis, Thomas H. Handbury, George H. Mendell, Henry Clay Newcomer, and Charles Francis Powell.
U.S. Army officer and engineer.
Collection material in English.
Keywords: Collingwood, Francis, -- 1834-1911.; Craighill, Wm. P. -- 1833-1909.; Dennis, William B., -- 1865-1937.; Handbury, Thomas H; Mendell, George H. -- 1831-1902.; Newcomer, Henry Clay, -- 1861-; Powell, Charles Francis, -- 1843-1907.; United States. -- Army. -- Corps of Engineers; Office of the Engineer Commissioner D.C.; United States Military Academy; Washington University (Saint Louis, Mo.); Canals -- Columbia River; Canals -- Oregon; Harbors -- Virginia -- Norfolk -- Design and construction; Locks (Hydraulic engineering) -- Oregon -- Cascade Locks -- Design and construction; Municipal engineering -- Washington (D.C.); River engineering -- Virginia; Army officers; Engineers